Analisis Penerapan Akuntansi Aset Tetap pada Kabupaten Pati Jawa Tengah - Silvi Purnama Devi; Ari Utomo Saputra (CV. Doki Course and Training, 2024)
Abstract : Fixed assets are resources that clearly have a valuable life of more than one year that are utilized or expected to be utilized in local government operations or for the common good. This research aims to determine the classification, measurement and disclosure of fixed asset bookkeeping applications at Pati Regency Regional Financial and Resource Institutions using government bookkeeping principles. The accounting rules governing the creation and presentation of government financial accounts are known as Government Accounting Standards (SAP). This study uses library research methodology in a qualitative way. This can be achieved by comparing how fixed asset accounting is implemented in the Regional Financial and Resource Institutions of Pati Regency using PSAP No. 07. The results of this research indicate that compliance with the preparation of financial reports at the Regional Asset Financial Institution in the Pati Region is in accordance with Government Accounting Standards Statement No. 07 of 2010 and Government Accounting Standards. In this research, we have complied with PSAP Policy No. 7 concerning reduction, termination, deletion, as well as classification, recognition and assessment. Abstrak : Aset tetap adalah sumber daya yang jelas memiliki umur yang berharga lebih dari satu tahun yang dimanfaatkan atau diharapkan untuk dimanfaatkan dalam operasi pemerintah setempat atau untuk kepentingan bersama. Penelitian ini bertujuan untuk menentukan klasifikasi, pengukuran dan pengungkapan aplikasi pembukuan aset tetap pada Lembaga Keuangan dan Sumber Daya Daerah Kabupaten Pati dengan menggunakan prinsip pembukuan pemerintah. Aturan akuntansi yang mengatur penciptaan dan penyajian rekening keuangan pemerintah dikenal sebagai Standar Akuntansi Pemerintah (SAP). Studi ini menggunakan metodologi penelitian perpustakaan dengan cara yang kualitatif. Hal tersebut dapat dicapai dengan membandingkan bagaimana akuntansi aset tetap diterapkan di Lembaga Keuangan dan Sumber Daya Daerah Kabupaten Pati dengan menggunakan PSAP No. 07. Hasil dari penelitian ini menunjukkan bahwa kepatuhan penyusunan laporan keuangan pada Lembaga Keuangan Aset Regional Daerah Pati sesuai dengan Pernyataan Standar Akuntansi Pemerintah No. 07 tahun 2010 dan Standar Akuntansi Pemerintah. Dalam penelitian ini telah mematuhi Kebijakan PSAP No. 7 tentang pengurangan, penghentian, penghapusan, serta klasifikasi, pengakuan, dan penilaian.